A cluster of inappropriate shocks in a pediatric S-ICD patient - how to troubleshoot? - Christina Menexi; Mohamed ElRefai; David Farwell; Neil Srinivasan (Indian Pacing and Electrophysiology Journal, 2024)
We present the case of a 16-year-old male pediatric patient diagnosed with hypertrophic cardiomyopathy (HCM, identified as having a high risk of sudden cardiac death (SCD), who underwent a successful subcutaneous implantable cardiac defibrillator (S-ICD) implantation as a primary prevention measure in 2018.His past medical history included ADHD, Autism, and panic attacks. The patient experienced appropriate shocks that successfully terminated VF episodes. However, he also experienced multiple inappropriate shocks from the S-ICD, triggered by anxiety-induced tachycardia during panic episodes. Meticulous assessment of S-ICD tracings and electrocardiograms (ECGs) revealed the erroneous classification of sinus tachycardia as sustained ventricular tachycardia, leading to unwarranted therapeutic interventions.Clinical intervention involved reprogramming of the S-ICD, emphasizing the pivotal role of personalized device configuration in pediatric cases where fine margins matter. While literature on S-ICD use in pediatric populations remains limited, emerging registries underscore the efficacy and safety of S-ICDs in preventing sudden cardiac death while reducing complications associated with intravascular leads. This case underscores the critical nature of customized device programming in pediatric patients, underscoring S-ICDs as a practical defibrillation alternative that addresses distinct concerns within this cohort of patients.